AB1133 Epidemiological Comparative Analysis in a Large Cohort of Psoriatic Arthritis Patients: Results of the Spanish IMID Consortium. (9th June 2015) - Cañete, J.; Rodriguez, J.; Gratacos, J.; Queiro, R.; Montilla, C.; Torre-Alonso, J.C.; Pérez-Venegas, J.J.; Muñoz, S.; Fernández-Nebro, A.; González, C.; Roig, D.; Erra, A.; et al.
Abstract : Background: Psoriatic Arthritis (PsA) is a complex disease of unknown etiology, involving both genetic and environmental factors. Objectives: To analyze the more relevant epidemiological characteristics in a large cohort of patients with PsA and controls in the Spanish population. Methods: A cross-sectional, comparative, multicenter study of patients with PsA and hypernormal healthy subjects for IMID diseases was performed. All patients were recruited through the Immune-Mediated Inflammatory Diseases Consortium (IMIDC).The IMIDC is a network of Spanish biomedical researchers focused in the study of the molecular basis of immune-mediated inflammatory diseases. All patients included in the present study were selected from the outpatient clinics of 13 Rheumatology Departments at different Spanish University Hospitals. An epidemiological questionnaire developed by experts at DNA National Bank was applied to obtain all data. Results: 1, 602 PsA patients and 1, 558 healthy subjects were included. 53% of PsA patients and 60% of controls were male. The mean age of patients PsA patients and controls was 52±13 years and 49±7 years respectively. In the univariate analysis, we observed that the height and weight of the control subjects was significantly higher than in patients with PsA.The level of statistical significance was decreased by introducing gender and age as covariates.In our cohort, 55% of patients with PsA had no education or only primary education. Control subjects mostly had secondary or higher education.The physical exercise was significantly more frequent among controls. The gender and age affect the assessment of physical activity performed by both groups of patients.Regarding employment status, most patients with PsA (29%) and controls (44%) were external employers.Both PsA patients and controls (52%) most frequently use their private cars.The mean consumption of tobacco and alcohol was higher in the control group and the statistical significance was maintained in multivariate analysis.In both univariate and multivariate analysis, statistical differences in the average number of children and consumption of coffee were observed. Conclusions: In this large comparative study we describe for the first time the general epidemiological characteristics in patients with PsA and healthy subjects representative of the Spanish population.PsA patients are older, have an average number of children higher and lower consumption of alcohol and tobacco than controls. The influence of gender confirms the significance level of variables such as physical activity, weight and height. Disclosure of Interest: None declared